HUBUNGAN ANTARA BERAT DENGAN VOLUME KAYU ACACIA MANGIUM DI SUBANJERIJI, SUMATERA SELATAN: STUDI KASUS DI PT MHP - Apul Sianturi (Jurnal Penelitian Hasil Hutan, 2003)
This study evaluated a method for estimating relationship between weight and volume of log of Acacia mangium. DBH of 50 trees (planted in 1991) in a sample plot in Subanjeriji had been measured, and the trees were then felled and bucked into 2.50 m logs upto a limit diameter of 8 cm. Diameter of each log was measured al both ends, and diameter of log was the mean of both ends diameter. The volume of logs was calculated by using formula of V = π R2 L. The mean of the log volume were 0.0485 m3 and 0.039 m3 for logs with bark and logs without bark respectively, and the mean of the log weight were 0.02846 ton and 0.025298 ton for logs with bark and logs without bark respectively. The relationship between the weight and volume of logs could be drawn by the formulas: B1 = 0.65 V, with t = 100.89 and r = 0.93B2 = 0.59 V1, with t = 94.61 and r = 0.92B3 = 0.56 V, with t = 58.18 and r = 0.82Since t0,01 is equal to 2.338 on 386 degrees of freedom, the coefficient of the three regressions are highly significant. Where B1 is the weight of logs with bark, and B2, and B3 are both the weight of logs without bark, and V and V1 are the volume of logs with and without bark respectively. The smallest convertion from volume to weight (density) is 0,56 ton/m3 that is for weight of logs without bark to logs with bark. Since the raw materials for pulp industry are logs without bark, the convertion from volume of logs with bark lo weight of logs without bark should use density value of 0.56 ton/m3.The staplemeter unit (sm) used by PT Musi Hulan Persada (PT MHP) as a tool for measuring the logs volume is miss used for the mean of tonage of weigt which transported by truck was 43.15 tonnes with the mean of estimated log volume was 77.65 sm. By using density of 0.56 ton/m3 the mean logs volume should be 76.75 m3 instead of 77.65 sm. Therefore the estimated volume should be in m3 instead of sm.